Twelve Good Men and True - J. S. Cockburn, Thomas A. Green (Princeton University Press, 2014)
This collection of essays on the English criminal trial jury originated in a panel held at the 1983 conference of the American Society for Legal History. On that occasion the editors and one of the contributors, John Beattie, addressed, inter alia, two closely related questions: Who were the jurors? and, How did the institution of the jury trial function? The second question commanded the greater interest—of both the panel and the audience—but it became clear that in order to answer that question fully, one had to know the answer to the first question. Given the demands of such an undertaking, and possible variations in local experience, it seemed appropriate to commission from interested scholars a range of essays on jury composition and its implications for the nature of the criminal trial and the administration of the criminal law. The history of crime, the criminal law, and more broadly, the administration of criminal justice had already attracted the attention of English historians of all periods from the Middle Ages to modern times, and many of these scholars had, each for his own time and locale, mastered the kinds of records that can be made to reveal the status, wealth, residence, and degree of literacy (if any) of those called upon to serve as jurors in the criminal courts. It appeared likely that a sustained focus on these records would not only shed light on the changing contours of composition but would also illuminate some critical turning points in the administration of the criminal law. This has indeed turned out to be true. Each of the essays collected here stands on its own. Together they form a kind of continuous history, although there are inevitable gaps, questions posed but left unanswered, and, at times, conflicting streams of emphasis or interpretation. A brief summary of their contents will aid selective readers who wish to know what is relevant to them as well as readers who are prepared to examine all the trees but who wonder in what forest they are wandering. The essays fall into three main periods: the medieval, the early modern, and the late seventeenth and eighteenth centuries. Individually, they may be epitomized as follows.